2022
DOI: 10.1111/codi.16118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative stoma site marking on risk of stoma‐related complications in patients with intestinal ostomy — A systematic review and meta‐analysis

Abstract: Aim This systematic review and meta‐analysis aimed to investigate the effect of preoperative stoma site marking on stoma‐related complications in patients with intestinal ostomy. Methods MEDLINE, Embase, CENTRAL, CINHAL, and Google Scholar were searched up to August 2021 for randomised controlled trials (RCTs) and nonrandomised studies of interventions (NRSI) that involved patients with intestinal ostomies comparing preoperative stoma site marking to no marking and which reported at least one patient‐relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…However, these studies generally investigated stoma complication risk factors using elective surgery cohorts or combined cohorts of elective with emergency surgeries. [5][6][7][8][9][10]13,20,21 The clinical significance of stoma site marking specifically in emergency stoma creation was not extensively addressed as only a small population received stoma marking prior to emergency surgery. The effects of preoperative stoma site marking on postoperative complications were investigated by analyzing exclusively patients who received urgent ostomy formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies generally investigated stoma complication risk factors using elective surgery cohorts or combined cohorts of elective with emergency surgeries. [5][6][7][8][9][10]13,20,21 The clinical significance of stoma site marking specifically in emergency stoma creation was not extensively addressed as only a small population received stoma marking prior to emergency surgery. The effects of preoperative stoma site marking on postoperative complications were investigated by analyzing exclusively patients who received urgent ostomy formation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8]11,12 A recent meta-analysis also showed that stoma site marking might reduce the risk of stoma-related complications. 13 Intensive interdisciplinary care before emergency surgery is essential to provide optimal care for stoma patients. However, due to limited time and staff, stoma site marking may not be routinely performed before emergency surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis performed showed that preoperative stoma marking can also decrease the risk of stoma-related complications. 53…”
Section: Stoma Site Markingmentioning
confidence: 99%
“…Several potential factors have been identified which may improve the patient experience after stoma formation in the elective setting across the perioperative journey. Preoperative stoma marking can reduce the risk of stoma‐related complications and has been shown to improve HR‐QoL [11]. Specific perioperative techniques, such as optimal stoma creation with minimal tension or a laparoscopic approach, may minimize perioperative complications [2].…”
Section: Introductionmentioning
confidence: 99%